A synergistic lightning-resistant composite material and preparation method thereof
By introducing conductive carbon nanomaterials into the resin of the composite material and designing conductive layers between the fiber layups, the problem of insufficient conductive connection of the composite material during lightning strikes is solved, and the thickness conductivity and lightning resistance are significantly improved.
Patent Information
- Application Number
- CN202211157919.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-22
AI Technical Summary
When composite materials are struck by lightning, due to the insulation of the resin, the conductive connection between internal carbon fibers is poor, resulting in high resistance, making it difficult for composite materials to effectively divert lightning current, and breakdown and burn-through damage are prone to occur.
By introducing conductive carbon nanomaterials into the resin and designing conductive layers between the fiber layups, a coordinated lightning strike-resistant composite material is formed. The content of the conductive carbon nanomaterial is 0.5 to 7 wt%, the thickness of the conductive layer is 6 to 50 μm, and the materials include carbon nanotubes, metal-plated carbon nanotubes, graphene, carbon nanofibers, etc.
It significantly improves the thickness conductivity of the composite material and enhances the lightning resistance, so that the composite material can more effectively dissipate lightning current and reduce lightning damage.
Smart Images

Figure CN115384133B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of structural composite materials, and relates to a synergistic lightning-resistant composite material and a preparation method thereof. Background Art
[0002] The lightning resistance of composite materials is one of the important issues faced by composite materials in the application of aviation and wind power. When a composite material is struck by lightning, due to the insulation of the resin itself, the conductive connection between the internal carbon fibers is poor. Therefore, the composite material has a higher resistance in the vertical fiber direction and an even higher resistance in the thickness direction. The high resistance in these two directions makes it difficult for the composite material to effectively conduct the lightning current. The overloaded current easily breaks down in the high-resistance thickness direction, causing the composite material to delaminate. At the same time, the near-surface fiber layer with lower resistance is burned through due to the passage of excessive current.
[0003] Most traditional composite lightning protection technologies use a method of adding a lightning protection layer to the surface of the composite material, that is, a highly conductive conductive layer is applied to the surface of the composite material as a lightning sacrificial layer. Currently, mature protective layer materials include: metal meshes including copper mesh and aluminum mesh, metal aluminum and copper coatings, and lightweight and highly conductive metal-coated non-woven fabrics developed in recent years. However, these additional surface layers have some disadvantages, such as increased weight and difficult process coverage. In the past 10 to 20 years, the development of structural-functional integrated composite materials has become the main direction, and structural composite materials with high lightning resistance have become the focus of academic and industrial attention. A large number of literature studies have shown that the most important factors affecting the lightning resistance of composite materials themselves are the surface conductivity and thickness conductivity of the composite materials. Improving the thickness conductivity of composite materials through various means has become a hot topic of research.
[0004] The main methods for improving the thickness-wise conductivity of composite materials include the following: (1) introducing conductive nanomaterials into the resin. However, the improvement in conductivity is usually very limited. For example, when 2 wt% of single-walled carbon nanotubes are introduced into the composite material, the thickness-wise conductivity of the composite material is almost not increased, only 0.018 S / cm (J. Compos. Mater. 45 (2011) 1109–1120.), and when 3 wt% of conductive reinforcing carbon black is introduced into the resin, the thickness-wise conductivity of the composite material is 0.56 S / cm (Composites Science and Technology, 2012, 72 (3): 412-420); (2) introducing conductive nanomaterials or conductive thin layer materials between layers, such as inserting nickel-plated carbon fiber powder between the layers of the composite material, the thickness-wise conductivity of the composite material is 0.622 S / cm (self-made material), and inserting 150 μm thick buckypaper between all layers, the thickness-wise conductivity of the composite material is 0.52 S / cm (Composite Structures, 2019, 210:581–589). In these technologies, the conductivity of the composite material through the thickness did not exceed 1S / cm, indicating that the conductivity was also limited by the interlayer conductive layer structure and the interlayer interface between the fiber layers. During a lightning strike, these higher resistance areas hinder the current from dissipating internally and become the focus of lightning damage. Summary of the invention
[0005] The present invention mainly aims at the above problems and proposes a synergistic lightning-resistant composite material and a preparation method thereof, the purpose of which is to improve the thickness-wise conductivity of the composite material and greatly enhance the lightning-resistant performance.
[0006] To achieve the above-mentioned purpose, the present invention provides a synergistic lightning-resistant composite material, which at least includes: a resin, a fiber ply, and a conductive layer located between the fiber plies; wherein the resin contains a conductive carbon nanomaterial, the content of the conductive carbon nanomaterial in the resin is 0.5-7wt%, the thickness of the conductive layer between the fiber plies is 6-50μm, and the conductive carbon nanomaterial is one of carbon nanotubes, metal-plated carbon nanotubes, graphene, metal-plated graphene, carbon nanofibers, metal-plated carbon nanofibers, conductive carbon black, or a mixture thereof.
[0007] Furthermore, the composite material contains a conductive layer between all fiber layers, or the composite material contains a conductive layer between each layer at least 0.6 mm thick from the outer surface to the inside.
[0008] Furthermore, the conductive carbon nanomaterial contained in the resin is metal-plated carbon nanofibers, and the total amount of the metal-plated carbon nanofibers is 0.25 to 7 wt% of the resin; or the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanofibers, carbon nanotubes, graphene, and carbon nanofibers, wherein the total content of the mixture is 0 to 2 wt% of the resin.
[0009] Furthermore, the conductive carbon nanomaterial contained in the resin is one of carbon nanotubes, graphene, carbon nanofibers or a mixture thereof, and the total amount of the carbon nanomaterial is 2-7 wt % of the resin.
[0010] Furthermore, the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanofibers and graphene or metal-plated carbon nanotubes, wherein the amount of the metal-plated carbon nanofibers is 0.25-5wt% of the resin, and the amount of the graphene or metal-plated carbon nanotubes is 0.25-2wt% of the resin.
[0011] Furthermore, the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanotubes and carbon nanofibers or graphene, wherein the amount of the metal-plated carbon nanotubes is 0.25-4wt% of the resin, and the amount of the carbon nanofibers or graphene is 0.25-3wt% of the resin.
[0012] Furthermore, the conductive layer between the fiber layers is a thin layer of conductive non-woven fabric, or a thin layer of carbon nanomaterial, or a thin layer of conductive non-woven fabric and carbon nanomaterial resin composite; wherein, when the conductive layer is a thin layer of conductive non-woven fabric, the thickness of the conductive layer is 10 to 50 μm, and the electrical conductivity is between 10 and 1000 S / cm; when the conductive layer is a thin layer of carbon nanomaterial, the thickness of the conductive layer is 5 to 55 μm, and the electrical conductivity is between 20 and 2000 S / cm; when the conductive layer is a thin layer of conductive non-woven fabric and carbon nanomaterial resin composite, the thickness of the conductive layer is 10 to 50 μm, the electrical conductivity of the conductive non-woven fabric is between 10 and 1000 S / cm, and the carbon nanomaterial content in the resin is higher than 20wt%.
[0013] Furthermore, the conductive layer between the fiber layers is a nano conductive non-woven fabric, and its structural form is: conductive organic nano non-woven fabric, metal conductive modified organic nano fiber non-woven fabric, hybrid conductive non-woven fabric of organic nano fiber and carbon nano material.
[0014] To achieve the above object, the present invention provides a method for preparing a synergistic lightning-resistant composite material, the method comprising:
[0015] Prepare or use an existing resin containing conductive carbon nanomaterials, and prepare a corresponding conductive modified prepreg by prepreg molding process and continuous fiber composite, wherein the content of the conductive carbon nanomaterials in the resin is 0.5-7wt%;
[0016] The surface of the conductive modified prepreg is coated or paved with a conductive thin layer having a thickness of 6 to 50 μm to obtain a nano-modified epoxy resin prepreg with a conductive layer on the surface;
[0017] Laying up the nano-modified epoxy resin prepreg with a conductive layer on the surface to obtain a preform;
[0018] The preform obtained by stacking is formed according to a composite material forming process to obtain the synergistic lightning-resistant composite material.
[0019] Furthermore, the conductive carbon nanomaterial is one of carbon nanotubes, metal-coated carbon nanotubes, graphene, metal-coated graphene, carbon nanofibers, metal-coated carbon nanofibers, conductive carbon black, or a mixture thereof.
[0020] The above technical solution of the present invention has the following advantages: it utilizes the good permeability of the carbon nanomaterial in the resin and designs the conductivity of the interlayer conductive structure, thereby improving the conductive connectivity between the fiber layer and the interlayer, so that the thickness conductivity of the final composite material is greatly improved, and by optimizing the conductivity of the interlayer conductive thin layer and the composition of the nanomaterial in the resin, the dissipation characteristics of the lightning current are optimized, so that the final composite material has good lightning resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structural composition of a synergistic lightning-resistant composite material of the present invention.
[0022] Figure 2 This is a comparison diagram of surface damage characteristics of the composite material in the embodiment of the present invention after being subjected to a simulated 2A zone lightning strike test.
[0023] Figure 3 A flow chart of a method for preparing a synergistic lightning-resistant composite material according to an embodiment of the present disclosure is shown.
[0024] In the figure: 1. Resin; 2. Fiber layer; 3. Conductive layer; 4. Conductive carbon nanomaterial. DETAILED DESCRIPTION
[0025] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0026] In the description of the present invention, it is necessary to understand that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0027] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0028] At present, it is difficult to achieve very high thickness-wise conductivity through conductive modification of a single region. It is necessary to establish a new conductive structure of composite materials in order to further improve the thickness-wise conductivity.
[0029] In view of the shortcomings of the prior art, the present invention proposes a synergistic lightning-resistant composite material, such as Figure 1 As shown, the composite material at least includes: a resin 1, a fiber ply 2, and a conductive layer 3 located between the fiber plies; wherein the resin 1 contains a conductive carbon nanomaterial 4, the content of the conductive carbon nanomaterial 4 in the resin 1 is 0.5-7wt%, and the thickness of the conductive layer 3 between the fiber plies 2 is 6-50μm.
[0030] In the above implementation, the nano-modified resin 1 and the relatively continuous conductive layer 3 structure between the layers are used to effectively improve the conductive connectivity inside the fiber layer 2, and improve the conductive continuity of the interface between the fiber layer 2 and the conductive structure between the layers. The fiber layer 2 of this type of synergistic lightning-resistant composite material has enriched and uniformly dispersed conductive carbon nanomaterials 4 near the surface, and a relatively continuous conductive layer 3 between the layers. The conductive carbon nanomaterials 4 near the surface of the fiber layer 2 play a good conductive connection role at the interface between the layers, thereby effectively improving the thickness conductivity of the composite material and greatly enhancing the lightning resistance performance.
[0031] From the above description, it can be seen that, limited by the conductive structural characteristics of composite materials, it is difficult to achieve high thickness conductivity through conductive modification of a single region at present. This is because when a single interlayer conductive layer is used, the conductive layer with poor interlayer deformability is difficult to form nano-scale conductive contact with the larger diameter carbon fiber, resulting in a higher resistance at the interlayer interface.
[0032] When using the method of using resin-dispersed carbon nanomaterials in coordination with the interlayer conductive layer. It is observed that in the composite material, the carbon nanomaterials in the resin are subject to the filtration effect of the carbon fiber layer and tend to be enriched at the interlayer interface. Usually, when a small amount of carbon nanomaterials is added to the resin, the conductivity is much lower than the thickness-wise conductivity of the composite material itself with higher conductivity. This is also the reason why the modification of resin carbon nanomaterials has little effect on conductivity in most literatures. In the technical solution of the present embodiment, the carbon nanomaterials are subject to the filtration effect of the interlayer conductive layer and the carbon fiber layer, and are easily enriched at the interlayer interface. This enrichment effect enhances the conductivity of the interface area and improves the thickness-wise conductivity.
[0033] However, if the conductivity enhancement effect produced by this enrichment effect is to be sufficient to affect the conductivity of the composite material, further improvements need to be made to the type, composition and content of carbon nanomaterials.
[0034] Typically, when the content of conductive carbon nanomaterial 4 in the resin is low, the improvement effect is not obvious, because the enrichment degree of conductive carbon nanomaterial 4 generated by the filtration effect is not enough to make its conductivity exceed the conductivity of the composite material itself. It was found through observation that when a synergistic effect occurs, the content of conductive carbon nanomaterial 4 in the resin 1 needs to exceed a threshold value, but this threshold value is also related to the structural characteristics of the interlayer conductive layer and the type of carbon nanomaterial. Preferably, when metal-plated carbon nanomaterials are used, the thickness-wise conductivity can be significantly improved at a lower content (such as 1wt%, at which time the achievable enrichment degree is low). If only unmodified carbon nanomaterials are used, it is necessary to reach more than 2wt% to effectively improve the thickness-wise conductivity, and more preferably 3wt% and above. The synergy of a variety of nanomaterials of different sizes helps to improve conductivity, such as a combination of metal-plated carbon nanofibers and carbon nanotubes, graphene, a combination of metal-plated carbon nanotubes and carbon nanofibers, graphene, etc.
[0035] In this regard, the present embodiment provides several synergistic materials that can help provide conductivity. For example, the conductive carbon nanomaterial 4 can be one of carbon nanotubes, metal-coated carbon nanotubes, graphene, metal-coated graphene, carbon nanofibers, metal-coated carbon nanofibers, conductive carbon black, or a mixture thereof.
[0036] The composition of the conductive carbon nanomaterial 4 and the proportion of a certain component thereof will be described in detail below with reference to specific examples. It should be noted that the composition of the conductive carbon nanomaterial 4 is not limited to this.
[0037] Composition method 1: When the conductive carbon nanomaterial 4 contained in the resin 1 is one of metal-plated carbon nanotubes, metal-plated graphene, metal-plated carbon nanofibers, or a mixture thereof, the total amount of the metal-plated carbon nanomaterial is 0.25-7wt% of the resin. In addition to the metal-plated carbon nanomaterial, the conductive carbon nanomaterial may also contain or not contain a mixture of conventional carbon nanotubes, graphene, and carbon nanofibers, with a total content of 0-2wt% of the resin.
[0038] Composition method 2: When the conductive carbon nanomaterial 4 contained in the resin 1 is one of carbon nanotubes, graphene, carbon nanofibers or a mixture thereof, the total amount of the conductive carbon nanomaterial is 2-7 wt % of the resin.
[0039] Composition method three: When the conductive carbon nanomaterial 4 contained in the resin 1 is a mixture of metal-plated carbon nanofibers and graphene or metal-plated carbon nanotubes, the amount of metal-plated carbon nanofibers is 0.25-5wt% of the resin, and the amount of graphene or metal-plated carbon nanotubes is 0.25-2wt% of the resin.
[0040] Composition method 4: When the conductive carbon nanomaterial 4 contained in the resin 1 is a mixture of metal-plated carbon nanotubes and carbon nanofibers or graphene, the amount of the metal-plated carbon nanotubes is 0.25-4wt% of the resin, and the amount of the carbon nanofibers or graphene is 0.25-3wt% of the resin.
[0041] In addition, the thickness of the interlayer conductive layer 3 is also an important factor affecting the conductivity. Increasing the thickness will affect the performance of the composite material. Too low a thickness will not significantly improve the conductivity. The location, material and thickness of the conductive layer 3 need to be optimized.
[0042] The location of the conductive layer 3 in the fiber layer 2 will be described in detail below with reference to specific examples.
[0043] In some embodiments, the composite material contains a conductive layer 3 between all fiber plies 2, or each layer of the composite material at least 0.6 mm thick from the outer surface of the composite material contains a conductive layer 3, and the rest of the composite material does not contain a conductive layer 3.
[0044] The material and thickness of the conductive layer 3 will be described in detail below with reference to specific examples.
[0045] In some embodiments, the thickness of the conductive layer 3 preferably ranges from 6 μm to 50 μm. When it comes to lightning protection applications, the interlayer conductive layer also needs to be controlled within a certain range. Too high or too low interlayer conductivity will lead to a decrease in lightning protection performance and an increase in actual damage. The preferred conductivity range is between 10 and 1000 S / cm. For a one-dimensional carbon nanofilm with a very small diameter, it has a higher current bearing and dissipation capacity, and the preferred conductivity range is between 20 and 2000 S / cm. However, the thickness of the conductive layer 3 needs to be adapted to the selected material.
[0046] As a preferred embodiment of the above embodiment, when the conductive layer 3 between the fiber plies 2 is a conductive non-woven fabric, the thickness of the conductive non-woven fabric is 10 to 50 μm, and the conductivity of the conductive non-woven fabric is between 10 and 1000 S / cm; when the conductive layer 3 between the fiber plies 2 is a thin layer of carbon nanomaterial, the thickness of the conductive layer 3 is 5 to 50 μm, and the conductivity is between 20 and 2000 S / cm.
[0047] As another preferred embodiment of the above embodiment, when the conductive layer 3 between the fiber plies 2 is a composite of a conductive non-woven fabric and a resin with a high carbon nanomaterial content, the thickness of the conductive layer 3 is 10 to 50 μm, the conductivity of the conductive non-woven fabric is between 10 and 1000 S / cm, and the carbon nanomaterial content in the resin is higher than 20 wt%.
[0048] As another preferred embodiment of the above embodiment, the conductive layer 3 between the fiber plies 2 is a nano-conductive non-woven fabric, and its structural form is: conductive organic nano-non-woven fabric, metal conductive modified organic nanofiber non-woven fabric, hybrid conductive non-woven fabric of organic nanofiber and carbon nanomaterial. The conductive layer with the above structural characteristics improves the ability of the composite material to dissipate lightning current, while improving the interlayer mechanical properties, and lightning damage is better suppressed.
[0049] Through the design of the content of the conductive carbon nanomaterial 4 in the resin 1 and the thickness of the conductive layer 3 between the fiber layers 2 in the above embodiment, the thickness-direction conductivity of the composite material obtained in this embodiment is significantly higher than the conductivity that can be achieved after the introduction of carbon nanomaterial modification in conventional literature, and the typical conductivity can reach more than 1S / cm. A typical synergistic lightning protection composite material effect is compared with a single nano-modified composite material. Figure 2 From the comparison diagram of surface damage characteristics of the composite material after the simulated 2A zone lightning strike test, it can be seen that the composite material with synergistic lightning resistance of this embodiment has better effect than the composite material with single nano modification.
[0050] In one aspect of the present invention, a method for preparing a synergistic lightning-resistant composite material is provided. The synergistic lightning-resistant composite material prepared by the method can effectively improve the electrical conductivity connectivity within the fiber layer, and improve the interface electrical conductivity continuity between the fiber layer and the interlayer conductive structure.
[0051] In the method of the present invention, by adjusting the proportion of the mixed mixture, the formed synergistic lightning-resistant composite material can have good lightning-resistant performance in the external environment. In addition, by the method of the present invention, the conductive performance of the produced synergistic lightning-resistant composite material can be significantly improved. Since the synergistic lightning-resistant composite material formed by the method of the present invention has a high thickness-wise conductivity, it can be promoted in the fields of aviation, wind power, etc.
[0052] like Figure 3 As shown, the embodiment of the present application provides a method for preparing a synergistic lightning-resistant composite material, the method comprising:
[0053] Step S100: preparing or using an existing resin containing a conductive carbon nanomaterial, and preparing a corresponding conductive modified prepreg by a prepreg molding process and continuous fiber composite, wherein the content of the conductive carbon nanomaterial in the resin is 0.5-7wt%;
[0054] Step S200: coating or paving the surface of the conductive modified prepreg with a conductive thin layer having a thickness of 6 to 50 μm to obtain a nano-modified epoxy resin prepreg having a conductive layer on the surface;
[0055] Step S300: stacking the nano-modified epoxy resin prepreg with a conductive layer on the surface to obtain a preform;
[0056] Step S400: forming the preform obtained by stacking according to a composite material forming process to obtain the synergistic lightning-resistant composite material.
[0057] In the above steps S100 to S400, a method is provided to prepare or purchase a conductive carbon nanomaterial modified epoxy resin by itself or through commercial channels, wherein the content of the conductive carbon nanomaterial in the resin is 0.5-7wt%, and then the corresponding conductive modified prepreg is prepared by prepreg molding process and continuous fiber composite. The surface of the conductive modified prepreg is coated or paved with a conductive thin layer to obtain a synergistically modified prepreg, wherein the thickness of the conductive thin layer is 6-50μm. The synergistically modified prepreg is stacked into a preform according to the molding process of the composite material, and then the stacked preform is molded according to the molding process of the composite material. The conductive carbon nanomaterial is one of carbon nanotubes, metal-plated carbon nanotubes, graphene, metal-plated graphene, carbon nanofibers, metal-plated carbon nanofibers, conductive carbon black, or a mixture thereof.
[0058] The technical solution of the present disclosure will be described below with reference to specific embodiments.
[0059] Embodiment 1:
[0060] The implementation process of the technical solution of the present invention is as follows:
[0061] (1-1) preparing or commercially purchasing a carbon nanomaterial-modified epoxy resin, wherein 1.0 wt% of carbon nanotubes, 1.5 wt% of graphene, and 1 wt% of carbon nanofibers are uniformly dispersed in the epoxy resin, and preparing the nano-modified epoxy resin into a unidirectional T800 fiber prepreg, wherein the prepreg single layer thickness is 0.125 mm and the resin content is 34 wt%;
[0062] (1-2) Coating 5 wt% of carbon nanotube aqueous dispersion on the surface of the prepreg, with a coating amount of 10 g / m 2 After the coating layer is dried, the thickness of the carbon nanotube thin layer is about 25 μm, and the conductivity is 182 S / cm, thereby obtaining a nano-modified epoxy resin prepreg with a conductive layer on the surface;
[0063] (1-3) 16 sheets of T800 fiber-reinforced nano-modified epoxy resin prepreg with a surface carbon nanotube thin layer were cut and laid in the order of [45° / 0° / -45° / 90°] 2S The composite material preform is obtained by quasi-isotropic ply laying, and a thin layer of carbon nanotubes is controlled between each layer during ply laying. Then, the preform is formed according to the hot-pressing molding process required by the epoxy resin, and after the molding is completed, the preform is cooled to below 60°C, and the composite material is taken out to obtain a composite material with coordinated lightning resistance;
[0064] (1-4) The above (1-1) can also use 1wt% carbon nanotube single nano-dispersed epoxy resin, or 1.6wt% carbon nanotube and 2wt% graphene co-dispersed epoxy resin, and can also use 1.6wt% carbon nanotube, 1.4wt% graphene and 2wt% conductive carbon black ternary nano-dispersed epoxy resin.
[0065] (1-5) The above (1-2) can also use carbon nanotube-mixed polyaniline nano-conductive non-woven fabric with a thickness of 15 μm and a conductivity of 75 S / cm.
[0066] The synergistic lightning-resistant composite material obtained in this embodiment has good electrical conductivity and lightning-resistant performance. The electrical conductivity in the thickness direction of the composite material reaches 0.71S / cm, which is 7 times that of ordinary high-conductivity composite materials and more than 500 times that of ordinary low-conductivity composite materials. The damage to the composite material after being struck by lightning in the simulated aircraft 2A zone is significantly reduced compared with conventional composite materials.
[0067] Embodiment 2:
[0068] The implementation process of the technical solution of the present invention is as follows:
[0069] (2-1) preparing a carbon nanomaterial-modified epoxy resin, wherein silver-plated carbon nanofibers and metal-plated carbon nanotubes are uniformly dispersed in the epoxy resin, wherein the content of the silver-plated carbon nanofibers is 4.2wt%, and the content of the silver-plated carbon nanotubes is 1.5wt%. The nano-modified epoxy resin is prepared into a prepreg of unidirectional T700 fiber, wherein the single layer thickness of the prepreg is 0.125mm and the resin content is 34wt%;
[0070] (2-2) Cut 24 sheets of the silver-plated graphene / carbon nanotube hybrid epoxy resin with a surface conductive layer, and take 24 sheets of nickel-plated nylon non-woven fabric of the same size, the thickness of the non-woven fabric is 45 μm, and the surface conductivity is 1.5 Ω / sq or 0.5 Ω / sq. The plying order is [45° / 0° / -45° / 90°] 3S Quasi-isotropic ply laying obtains a composite material preform, and a layer of nickel-plated non-woven fabric is inserted between each layer of the composite material, and finally a layer of nickel-plated non-woven fabric is covered on the surface;
[0071] (2-3) The preform is molded according to the autoclave molding process required by the nano-modified epoxy resin. After molding, the preform is cooled to below 60° C., and the composite material is taken out to obtain a composite material with synergistic lightning resistance;
[0072] (2-4) The nickel-plated nylon nonwoven fabric of (2-2) above can be coated with the same resin containing 25 wt% carbon nanotubes diluted by solvent, and the coating amount of the resin is 30 g / m 2 After drying, it becomes a nickel-plated non-woven fabric composited with resin and high carbon nanomaterial content. The same method is used to intercalate and prepare the composite material.
[0073] The synergistic lightning-resistant composite material obtained in this embodiment has good electrical conductivity and lightning-resistant performance. The conductivity of the composite material in the thickness direction reaches 2.1S / cm, which is more than 20 times that of ordinary high-conductivity composite materials and more than 1500 times that of ordinary low-conductivity composite materials. The damage to the composite material after being struck by lightning in the simulated aircraft 2A zone is significantly suppressed. By using the composite conductive thin layer in (2-4), the composite material has more excellent lightning-resistant performance, and only has slight surface damage after being struck by lightning.
[0074] Embodiment 3:
[0075] The implementation process of the technical solution of the present invention is as follows:
[0076] (3-1) preparing a conductive carbon nano-modified epoxy resin, wherein 4 wt % nickel-plated carbon nanofibers and 1.5 wt % graphene are uniformly dispersed in the epoxy resin, and preparing the nano-modified epoxy resin into a unidirectional T800 fiber prepreg, wherein the prepreg single layer thickness is 0.125 mm and the resin content is 35 wt %;
[0077] (3-2) Coating the prepreg surface with an aqueous co-dispersion of carbon nanofibers and graphene, with a content ratio of 2:1, a total concentration of 6 wt %, and a total dry coating amount of 18 g / m 2 The coating layer has a thickness of about 50 μm after drying and an electrical conductivity of 80 S / cm, thereby obtaining a nano-modified epoxy resin prepreg with a conductive layer on the surface;
[0078] (3-3) 16 sheets of the hybrid epoxy resin prepreg with carbon nanofilm were cut and laid in the order of [45° / 0° / -45° / 90°] 2S The composite material preform is obtained by quasi-isotropic ply laying, and a conductive layer is controlled between each layer during ply laying; and then it is formed according to the hot-press molding process required by the epoxy resin. After molding, it is cooled to below 60°C, and the composite material is taken out to obtain a composite material with coordinated lightning resistance;
[0079] (3-4) The amounts of nickel-plated carbon nanofibers and graphene used in the above (3-1) may also be 2 wt% and 0.5 wt%, or 1.5 wt% and 1.5 wt%, respectively.
[0080] (3-5) The carbon nanomaterial coating used in the above (3-2) can also be a composite conductive nanofiber non-woven fabric prepared by blending carbon nanotubes and nylon nanofibers in a mass ratio of 1:3, with a thickness of 12 μm and a surface resistance of 15 Ω / sq.
[0081] The synergistic lightning-resistant composite material with carbon nanomaterial coating in this embodiment has good electrical conductivity and lightning-resistant performance, and relatively less weight gain. The conductivity in the thickness direction of the composite material reaches 1.39S / cm. The conductivity in the thickness direction of the composite material using composite conductive nanofiber non-woven fabric is 0.52S / cm, but has higher impact resistance.
[0082] Embodiment 4:
[0083] The implementation process of the technical solution of the present invention is as follows:
[0084] (4-1) adding silver-coated carbon nanotubes and graphene nanosheets to epoxy resin E54 at a ratio of 1.0 wt% and 0.7 wt%, respectively, and dispersing them uniformly; then adding diaminodiphenyl sulfone as a curing agent in an equivalent amount; and homogenizing to obtain an epoxy resin modified with silver-coated carbon nanotubes and graphene nanosheets; and preparing the nano-modified epoxy resin into a prepreg of unidirectional T700H fiber, wherein the single layer thickness of the prepreg is 0.167 mm and the resin content is 32 wt%;
[0085] (4-2) A layer of carbon nanotube film is covered on the surface of the prepreg. The thickness of the carbon nanotube film is 10 μm and the surface density is 3.5 g / m2 , the conductivity is 450S / cm, and a nano-conductive modified epoxy resin prepreg with a carbon nanotube conductive film on the surface is obtained;
[0086] (4-3) 16 sheets of the silver-coated carbon nanotube / graphene hybrid epoxy resin prepreg with carbon nanotube film and 16 sheets of conventional epoxy resin prepreg are cut and laid in the order of [45° / 0° / -45° / 90°] 4S Quasi-isotropic ply laying obtains a composite material preform, in which the conductive modified prepreg is located in the first 16 layers, and a layer of carbon nanotube film is controlled between each layer. The upper surface of the composite material is a carbon nanotube film, and the last 16 layers are conventional epoxy resin prepreg. Then, it is formed according to the autoclave molding process required by the epoxy resin. After molding, it is cooled to below 60°C, and after the composite material is taken out, a composite material with synergistic lightning resistance is obtained;
[0087] (4-4) The above (4-3) can also adopt a combination of 8 layers of conductive modified prepreg and 24 layers of conventional prepreg, wherein the conductive modified prepreg is located in the first 8 layers, and each layer of the first 8 layers is controlled to have a layer of carbon nanotube film, the upper surface of the composite material is a carbon nanotube film, and the last 24 layers are conventional epoxy resin prepreg;
[0088] (4-5) In the above (4-1), the graphene nanosheets may be replaced with carbon nanofibers with the same content.
[0089] The synergistic lightning-resistant composite material obtained in this embodiment has good electrical conductivity and lightning-resistant performance. After the composite material is struck by lightning in the 2A area of the aircraft, only the first layer suffers fiber breakage and resin ablation damage.
[0090] (4-6) The carbon nanotube film used in (4-3) can also have a thickness of 28 μm and a surface density of 10 g / m 2 , the number of intercalation layers is reduced to 8 layers.
[0091] (4-7) The carbon nanotube film used in (4-3) above may also be a composite film of graphene and carbon nanotubes, with a conductivity of 1100 S / cm, a thickness of 17 μm, and a surface density of 6 g / m 2 , the number of intercalation layers is 12.
[0092] (4-8) The carbon nanotube film used in (4-3) above can be replaced by a nano-silver-coated nylon non-woven fabric containing 70 wt% nickel-coated carbon nanotubes, with a thickness of 21 μm and a conductivity of 760 S / cm.
[0093] The synergistic lightning-resistant composite material obtained in this embodiment has good electrical conductivity and lightning-resistant performance. After the composite material was struck by lightning in the aircraft 2A area, only the first layer suffered fiber breakage and resin ablation damage. The composite material with a conductive layer made of nano-silver-plated nylon non-woven fabric with nickel-plated carbon nanotubes has higher interlayer fracture toughness.
[0094] Embodiment 5:
[0095] The implementation process of the technical solution of the present invention is as follows:
[0096] (5-1) adding silver-coated nanocarbon fibers, silver-coated graphene, and silver-coated carbon nanotubes to epoxy resin at a ratio of 3.0 wt%, 1.0 wt%, and 2.0 wt%, respectively, and dispersing them uniformly; then adding dicyandiamide as a curing agent in an equivalent amount; and then adding 10 wt% of a thermoplastic polyimide toughening agent; and homogenizing to obtain an epoxy resin co-modified with three silver-coated carbon nanomaterials; and preparing the nano-modified epoxy resin into a unidirectional CCF800H carbon fiber prepreg, wherein the prepreg single layer thickness is 0.125 mm and the resin content is 35 wt%;
[0097] (5-2) A layer of micron-sized powder formed by crushing carbon nanotube sponge is coated on the surface of the prepreg. The powder particles are about 0 to 15 μm and the powder density is 0.02 g / cm 3 , the total coating surface density is 7g / m 2 , obtaining a nano-conductive modified epoxy resin prepreg with carbon nanotube sponge powder on the surface;
[0098] (5-3) Cut 16 sheets of the conductive modified prepreg of the modified epoxy resin with carbon nanotube sponge and 16 sheets of conventional epoxy resin prepreg, and lay them in the order of [45° / 0° / -45° / 90°] 4S Quasi-isotropic ply laying obtains a composite material preform, in which the conductive modified prepreg is located in the first 16 layers, and each interlayer of the first 16 layers is controlled to have carbon nanotube sponge powder, and the last 16 layers of the preform are conventional epoxy resin prepreg. Then, the preform is formed according to the autoclave molding process required by the epoxy resin. After molding, it is cooled to below 60°C, and the composite material is taken out to obtain a composite material with synergistic lightning resistance;
[0099] (5-4) 0.5 wt% of carbon nanotubes or 0.5 wt% of carbon nanofibers can also be added to the epoxy resin in the above (5-1) for co-dispersion to form a conductive epoxy resin with a high carbon nanomaterial content.
[0100] Embodiment 6:
[0101] The implementation process of the technical solution of the present invention is as follows:
[0102] (6-1) preparing a nano-modified bismaleimide resin, wherein 1 wt% of silver-plated carbon nanofibers, 0.5 wt% of graphene and 1 wt% of carbon nanotubes are uniformly dispersed in the bismaleimide resin, and preparing a prepreg of GW3031 carbon fiber twill fabric with the multi-component nano-modified bismaleimide resin, wherein the prepreg has a single layer thickness of 0.190 mm and a resin content of 42 wt%;
[0103] (6-2) Applying an aqueous co-dispersion of carbon nanotubes and silver-coated graphene on the surface of the carbon fiber prepreg at a coating amount of 4 g / m 2 The coating layer has a thickness of about 10 μm after drying, and a nano-modified bismaleimide resin prepreg with a conductive layer on the surface is obtained;
[0104] (6-3) Cut 16 sheets of the multi-hybrid bismaleimide resin carbon fiber prepreg with a surface carbon nanomaterial conductive layer and lay them in the order of [45° / 0°] 4S The composite material preform is obtained by quasi-isotropic ply laying, and a conductive layer is controlled between each layer during ply laying; and then the preform is formed according to the hot-pressing molding process required by the bismaleimide resin. After molding, it is cooled to below 60°C, and the composite material is taken out to obtain a composite material with coordinated lightning protection;
[0105] The synergistic lightning-resistant composite material obtained in this embodiment has good electrical conductivity and lightning-resistant performance. The conductivity in the thickness direction of the composite material reaches 1.3S / cm, which is 10 times that of ordinary high-conductivity composite materials of this system. When the composite material is struck by lightning in the 2A zone of the aircraft, the sample plate has only slight resin ablation on the surface.
[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A synergistic lightning-resistant composite material, characterized in that: The synergistic lightning-resistant composite material comprises at least: a resin, a fiber ply, and a conductive layer between the fiber plies; wherein the resin contains a conductive carbon nanomaterial, and the thickness of the conductive layer between the fiber plies is 6 to 50 μm; The conductive carbon nanomaterial contained in the resin is one of metal-plated carbon nanotubes, metal-plated graphene, metal-plated carbon nanofibers or a mixture thereof, and the total amount of the metal-plated carbon nanomaterial is 0.25-7wt% of the resin; Alternatively, the conductive carbon nanomaterial contained in the resin is one of carbon nanotubes, graphene, carbon nanofibers or a mixture thereof, and the total amount of the conductive carbon nanomaterial is 2 to 7 wt % of the resin; Alternatively, the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanofibers and graphene, the amount of the metal-plated carbon nanofibers is 0.25 to 5 wt% of the resin, and the amount of the graphene is 0.25 to 2 wt% of the resin; Alternatively, the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanotubes and carbon nanofibers, the amount of the metal-plated carbon nanotubes is 0.25-4wt% of the resin, and the amount of the carbon nanofibers is 0.25-3wt% of the resin; Alternatively, the conductive carbon nanomaterial contained in the resin is a mixture of metal-plated carbon nanotubes and graphene, the amount of the metal-plated carbon nanotubes is 0.25-4wt% of the resin, and the amount of the graphene is 0.25-3wt% of the resin; The conductive layer between the fiber layers is a nano conductive non-woven fabric, and its structural form is: a metal conductive modified organic nano fiber non-woven fabric, a hybrid conductive non-woven fabric of organic nano fiber and carbon nano material; The preparation method of the synergistic lightning-resistant composite material comprises the following steps: Prepare or use existing resin containing conductive carbon nanomaterials, and prepare corresponding conductive modified prepregs by prepreg molding process and continuous fiber composite; The surface of the conductive modified prepreg is coated or paved with a conductive thin layer having a thickness of 6 to 50 μm to obtain a nano-modified prepreg with a conductive layer on the surface; Laying up the nano-modified prepreg with a conductive layer on the surface to obtain a preform; The preform obtained by stacking is formed according to a composite material forming process to obtain the synergistic lightning-resistant composite material.
2. The synergistic lightning-resistant composite material according to claim 1, characterized in that: The composite material contains a conductive layer between each fiber layer in an area at least 0.6 mm thick from the outer surface.
3. A synergistic lightning-resistant composite material as claimed in claim 2, characterized in that: The composite material contains a conductive layer between all fiber layers.
Citation Information
Patent Citations
Composite conductive film, its preparation method and its application
CN102785437A
Improved composite materials
CN105479830A
Cited By
Composite graphene lightning-resistant material and preparation method and application thereof
CN122706088A